Efficacy of various organic and biofertilizer on the growth and yield of Brassica oleracea L. (Cabbage) - Chanu Khuraijam Panthoi; Agrawal Shubhi; Bopche Vaibhav; Sharma Abha (BIO Web of Conferences, 2024)
Organic manures and biofertilizers are widely renowned as effective all-encompassing approaches to improving soil quality. They utilise the benefits of organic components such as residual plant waste, compost, and manure. The incorporation of organic matter improves the structure of the soil, encourages microbial activity, and releases nutrients gradually. As a result, the study was carried out to evaluate whether organic manures were suitable for growing cabbage. This study adopted a randomised block design and included six treatments: vermicompost, poultry manure, farm yard manure, vermicompost + azotobacter, poultry manure + azotobacter and a control. The study assessed the cabbage’s growth and yield characteristics, including height of the plant, number of leaves, head diameter, weight, and overall yield. The results of the study demonstrated that cabbage’s growth and yield performance were significantly impacted by the application of organic manures. The highest production was obtained from the vermicompost +azotobacter treatment, which was followed by vermicompost and poultry +azotobacter. The use of organic manures led to considerable improvements in plant weight, height, and head diameter. In conclusion, the study provides useful knowledge on growing cabbage using organic manures. Farmers, legislative leaders, and various other agricultural sector decision-makers could employ the results of the investigation to promote profitable and sustainable cabbage growing techniques.